Infamous bodies : early Black women's celebrity and the afterlives of rights - Pinto, Samantha (Duke University Press, 2020)
"INFAMOUS BODIES portrays five black women "celebrities" from the late-18th and 19th centuries whose histories and ongoing fame have generated new ways of imagining black feminist futures. Phillis Wheatley, Sally Hemings, Saartjie Baartman, Mary Seacole, and Sarah Bonetta have each become crucial figures for black feminists, who have frequently re-imagined these women's public and private lives, celebrating them as subjects who complicate a binary understanding of agency and subjection. Centering black women's lives at the fulcrum of developing freedom and rights discourses in the US and Europe, Samantha Pinto seeks to rewrite the history of modern nationhood through stories of black female subjectivity. The book's five chapters trace the historical significance of these figures, as well as the contemporary cultural artworks and performances that have rendered them celebrities for black feminist study. First, Pinto shows how Phillis Wheatley's fame has been essential to both American humanism and African diasporic conceptions of race and freedom. She then traces how the narratives surrounding Sally Hemings's relationship with Thomas Jefferson produce a dichotomy of unconsent/consent that arises out of humanist notions of freedom and respectability. Pinto counters these interpretations by considering reanimations of Hemings in various creative works. These new works point towards a politics of consent that does not relegate black women's bodies to sites of unfreedom. Next, Pinto considers William Dunlap, a white man put on trial for forcing Saartjie Baartman to perform on stage against her will; the trial hinged on the validity of her labor contract and her ability to consent to such a contract. For Pinto, the trial exposes contractual freedom as a fiction. Next, Pinto turns to Mary Seacole, a Jamaican-born British nurse and memoirist. Seacole has recently been revived as a British celebrity in the midst of contemporary debates around multiculturalism, as she has been imagined as a symbol of contemporary transnational capitalist success. Similarly, Sarah Bonetta, a formerly enslaved and orphaned Yoruba princess who became Queen Victoria's goddaughter, is narrated as a symbol of black autonomy and freedom in British history. Yet, for Pinto, popular narratives of both Seacole and Bonetta-including their proximity to whiteness and capital-reveal the complexities and hazards of corrective histories meant to repair racial injury. INFAMOUS BODIES offers a creative archival intervention that compels one to think about the black woman celebrity in new and necessary ways. It will appeal to an interdisciplinary audience, including those engaging in black studies, women's studies, literary studies, performance studies, and histories of the Black Atlantic"--